Design and fabrication of a generic 3D-printed silicone unilateral cleft lip and palate model. Issue 10 (October 2019) - Riedle, Hannah; Burkhardt, Andrea E.; Seitz, Vera; Pachaly, Bernd; Reid, Russell R.; Lee, Justine C.; Franke, Jörg E.
Summary: The complexity of plastic surgery procedures often requires visualization of the anatomy in three dimensions and therefore demands the development of new and innovative teaching methods. This work describes the development and manufacture of a 3D silicone cleft lip and palate (CLP) model evaluated by surgical residents on its similarity to the biological model. Thirty unilateral CLP models were created and distributed to residents at two different institutions. The model was based on an adult CT scan that was manipulated to resemble an infant with a complete unilateral CLP. This digital model was directly printed in silicone elastomer pieces and later assembled. The residents rated the model based on its realistic value as well as whether or not they felt it improved their surgical technique. Twenty residents used the model to simulate a CLP repair. The structure of the model was rated as fairly realistic while both the material and assembly of the model require improvement in subsequent manufacturing. Post simulation, residents rated the model highly for how accurately it simulated the surgical procedure. An accurate 3D silicone unilateral cleft lip and palate replica was successfully created for educational purposes. This new approach combines a flexible generic design with automated manufacture.